1996
DOI: 10.1128/aem.62.10.3722-3726.1996
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus thuringiensis HD-73 Spores Have Surface-Localized Cry1Ac Toxin: Physiological and Pathogenic Consequences

Abstract: Spores from Cry ؉ strains of Bacillus thuringiensis bound fluorescein isothiocyanate-labeled antibodies specific for the 65-kDa activated Cry 1Ac toxin, whereas spores from Bacillus cereus and Cry ؊ strains of B. thuringiensis did not. The Cry ؉ spores could be activated for germination by alkaline conditions (pH 10.3), whereas Cry ؊ spores could not. Once the surrounding exosporia had been removed or permeabilized, Cry ؉ spores were able to bind the toxin receptor(s) from insect gut brush border membrane vesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…In addition to being organized into a structured parasporal crystal, the δ‐endotoxins can also be embedded in the spore wall. Du and Nickerson (1996) found that germination of spores of B. thuringiensis ssp. kurstaki HD‐73 with Cry1Ac embedded in the spore coat could be activated by alkaline conditions, whereas selected Cry‐negative B. thuringiensis ssp.…”
Section: Properties Of Bacillus Thuringiensismentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to being organized into a structured parasporal crystal, the δ‐endotoxins can also be embedded in the spore wall. Du and Nickerson (1996) found that germination of spores of B. thuringiensis ssp. kurstaki HD‐73 with Cry1Ac embedded in the spore coat could be activated by alkaline conditions, whereas selected Cry‐negative B. thuringiensis ssp.…”
Section: Properties Of Bacillus Thuringiensismentioning
confidence: 99%
“…kurstaki HD‐73 could not. Furthermore, cry + spores could bind to toxin receptors in brush border membrane preparations, a binding that also stimulated spore germination (Du and Nickerson, 1996). This phenomenon may, in part, explain the evolutionary advantage of possessing δ‐endotoxins, namely the ability for B. thuringiensis to germinate faster than B. cereus and thus have a greater chance to proliferate and dominate in an insect gut, even in the absence of the crystalline δ‐endotoxins.…”
Section: Properties Of Bacillus Thuringiensismentioning
confidence: 99%
“…The function of the exosporium is unknown, although it has been speculated that it may be the basis of the extremely hydrophobic nature of these spores (Koshikawa et al 1989) and may therefore have a role in adhesion. It has also been proposed that, in some B. thuringiensis species, the insecticidal crystal toxins are protected from the environment by enclosure within the exosporium (Du and Nickerson 1996). Thus the possession of an exosporium by B. thuringiensis and other members of the B. cereus family may enhance the pathogenicity of these organisms.…”
Section: Introductionmentioning
confidence: 99%
“…This is toxic to the lepidopteran species. 6 The cry1ac gene has been expressed in several transgenic crop plants of which Bt cotton and Bt corn have been released for cultivation in many countries. 7 Cotton (Gossypium hirsutum), an important fiber crop, is highly susceptible to a large number of lepidopteran pests, and a major one in the Indian subcontinent is Helicoverpa armigera.…”
Section: Introductionmentioning
confidence: 99%